The level of vascular endothelial growth factor in peripheral blood of type 2 diabetic patients depending on kidney functional state - Topchii, I.; Shcherban, T.; Galchinska, V.; Semenovykh, P.; Savicheva, K. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Abstract. The aim of the study was to assess a serum level of vascular endothelial growth factor (VEGF) in type 2 diabetic patients depending on kidney function. Methods: we examined 66 type 2 diabetic patients and 20 healthy control subjects. Depending on the presence of albuminuria and glomerular filtration rate (GFR) level, patients with diabetes mellitus (DM) were divided into the following groups: group I - patients with type 2 DM without signs of nephropathy – normal GFR without albuminuria (n = 26); group ІІ - patients with type 2 DM with normal GFR and albuminuria (n = 22); group III - patients with type 2 DM with reduced GFR and albuminuria (n = 18). ІV group - patients with acute coronary syndrome (n = 26). The concentration of the VEGF was determined by enzyme-linked immunosorbent assay. The glomerular filtration rate (GFR) was calculated using the CKD EPI formula (KDIGO 2012). Results: serum VEGF level in patients with diabetic nephropathy (DN) was significantly increased depending on kidney function. VEGF positively correlated with urine albumin and serum creatinine levels and the negative correlation with GFR was found. These findings prove the undeniable role of kidneys in the development of renocardial syndrome in patients with DN. VEGF levels positively correlated with glycosylated hemoglobin and total cholesterol, indicating an unconditional dependence of endothelial dysfunction on lipid and glucose metabolism disorders. Conclusions: Increased levels of VEGF in type 2 diabetic patients without clinical signs of kidney damage may indicate the development of subclinical renal dysfunction. Blood VEGF in patients with DN may be an integral marker of endothelial dysfunction and pathological angiogenesis. Our findings suggest that determination of serum VEGF level in patients with DN may have practical use as an early predictor of cardiac disruption, estimation of the prognosis, as well as improvement of cardionephroprotective strategy.